Gerenciamento de riscos nas compras públicas de medicamentos oncológicos: estratégia e métodos para mitigação de falhas - Virginia Luiz de Sousa; Jorge Carlos Santos da Costa; Elezer Monte Blanco Lemes (Vigilância Sanitária em Debate, 2026)
Introduction: Public procurement of oncology medicines represents a significant share of healthcare expenditures and plays a crucial role in ensuring universal access to essential therapies. However, the bidding process is subject to failures that compromise efficiency, transparency, and patient safety. Objectives: To develop and apply a risk management (RM) model adapted to the reality of public procurement of oncology medicines, based on nationally and internationally recognized methodologies. Method: Case study of an applied, exploratory, and descriptive nature, with a qualitative approach, grounded in bibliographic and documentary research and direct observations. Techniques such as process mapping, SWOT analysis, brainstorming, and adapted FMEA were used, integrated with the guidelines of ABNT NBR ISO 31000:2018, ABNT NBR IEC 31010:2021, and the Brazilian Federal Comptroller General’s Risk Management Manual (CGU, 2018). Results: A total of 65 hazards were identified in the routines of anticancer drug procurement. The control measures led to a positive reclassification of risks, with a significant shift from the most critical levels to categories of lower impact. Among the 65 identified hazards, 23 were classified as low risk, 35 as medium, 6 as high, and 1 as very high. After the implementation of the control measures, a marked improvement in the risk profile was observed, with 53 events classified as low risk, 9 as medium, 3 as high, and no events as very high risk. These results demonstrate the effectiveness of the actions, achieving the complete elimination of very high risks and a reduction greater than 70% in medium and high risks. Conclusions: The proposed model demonstrated potential to enhance governance, transparency, and efficiency in the public procurement of oncology medicines, in addition to contributing to the sustainability of the SUS.